2015
DOI: 10.1007/s10560-015-0412-6
|View full text |Cite
|
Sign up to set email alerts
|

Outpatient Dialectical Behavior Therapy for Adolescents Engaged in Deliberate Self-Harm: Conceptual and Methodological Considerations

Abstract: The current review examines conceptual and methodological issues related to the use of dialectical behavior therapy for adolescents (DBT-A) in treating youth who engage in deliberate self-harm. A comprehensive review of the literature identified six studies appropriate for the review. Results indicated several inconsistencies and limitations across studies including the mixing of various forms of self-harm; variations in diagnostic inclusion/exclusion criteria, insufficient use of standardized self-harm outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 75 publications
1
10
0
Order By: Relevance
“…We propose that these problems are due to limitations in the designs of these research studies that are related to monitoring and measuring self-injury in study participants. This explanation aligns with the findings in another study in which researchers identified substantial inadequacies in outcome research on DBT-A for self-injury, including a lack of consistency in inclusion criteria and inconsistent use of formalized assessments to measure self-injury (Freeman, James, Klein, Mayo, & Montgomery, 2016).…”
Section: Effectiveness Of Dialectical Behavior Therapy For Adolescentssupporting
confidence: 80%
“…We propose that these problems are due to limitations in the designs of these research studies that are related to monitoring and measuring self-injury in study participants. This explanation aligns with the findings in another study in which researchers identified substantial inadequacies in outcome research on DBT-A for self-injury, including a lack of consistency in inclusion criteria and inconsistent use of formalized assessments to measure self-injury (Freeman, James, Klein, Mayo, & Montgomery, 2016).…”
Section: Effectiveness Of Dialectical Behavior Therapy For Adolescentssupporting
confidence: 80%
“…In a review of six controlled trials, Freeman et al . () concluded that dialectical behaviour therapy and family therapy was an effective intervention for adolescents who had attempted suicide. It led to significant reductions in non‐suicidal self‐harming behaviour, suicidal ideation and depressive symptoms.…”
Section: Emotional Problemsmentioning
confidence: 99%
“…Both sets of factors are targeted in family-based treatment for self-harm in adolescence. A series of studies has found that a range of specialized systemic interventions improved the adjustment of adolescents who had self-harmed (Asarnow et al, 2011;Diamond et al, 2010;Freeman et al, 2016;Harrington et al, 1998;Huey et al, 2004;King et al, 2006King et al, , 2009Rotheram-Borus et al, 2000), although family interventions were not always more effective than alternative treatments in reducing recurrence of self-harm. For example, in a large (N5832) UK randomized controlled trial, Cottrell et al (2018) found that family therapy was no more effective than treatment-asusual in preventing repeated self-harm at eighteen months follow up.…”
Section: Self-harmmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment duration is one of the number of variations in DBT-A studies to date that needs to be addressed (e.g. Freeman, James, Klein, Mayo, & Montgomery, 2016;MacPherson, Cheavens, & Fristad, 2013). To the best of our knowledge, no empirical research has compared the effectiveness of 16-and 24-week DBT-A programmes.…”
Section: Introductionmentioning
confidence: 99%